Pakistani students' perceptions about their learning experience through video games: A qualitative case study. Issue 3 (29th November 2019) - Khalid, Tooba; Batool, Syeda Hina; Khalid, Ayesha; Saeed, Henna; Zaidi, Syed Waqas Hussain
Abstract : Purpose: The emergence of digital technological advances pushes educators for understanding and utilizing these technologies for classroom use. The current generation of teenagers has grown up in a networked world where everyone is immersed in technology-based gadgets in everyday life. Therefore, the purpose of this paper is to investigate video game-based academic and information literacy (IL) learning of teenagers of private schools of Lahore city. Lahore is the capital city of the province of Punjab. Literary works highlighted the importance of video games in developing academic and IL skills; therefore, the current research aims to reveal this fact in local context. Design/methodology/approach: The present study adopted qualitative research design and utilized phenomenological research method to achieve study's objectives. The data were collected through face-to-face interviews. The study participants were teenagers (aged 13‒19 years) of elite economic class of private schools where students normally owned latest video game gadgets. Findings: Based on the study findings, it is elucidated that playing video games has a positive impact on teenagers' learning, and it promotes quick thinking. The participants exert effort to achieve goals, take up challenges for completing different points at various stages of games and interact with online competitors. It enhanced their social communication, problem-solving and IL (searching/locating and evaluating) skills. Research limitations/implications: The present study has some limitations. First, sample is limited to elite economic private schools of Lahore. Second, the lack of availability of regular video game players has limited the sample size, as Pakistan is a developing country and limited numbers of teenagers use and can afford gaming gadgets. Lastly, the results of this study are based on students' perceptions, so there is a need to measure actual learning with assessments. Originality/value: The results of the study are beneficial for the game developers, teachers, librarians and parents. The education sector may support video games usability as learning tools.